Preparation method of high-safety ternary polymer and lithium battery

By covering ultra-high molecular weight polyethylene and carbon nanotube materials on the surface of the positive electrode material of the ternary polymer lithium battery, and using high-temperature dynamic coating technology to form a cladding layer with positive temperature coefficient effect, solving the safety risks of ternary polymer lithium battery catchment and explosion under extreme conditions, and achieving high safety performance of lithium batteries.

CN119650647APending Publication Date: 2025-03-18GUANGXI NEW-FORTUNE NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411823558.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Triple polymer lithium batteries are prone to fire and explosion under extreme test conditions, and the prior art has failed to effectively improve their safety performance.

Method used

By coating ultra-high molecular weight polyethylene and carbon nanotube materials on the surface of the ternary polymer positive electrode material, the ultra-high molecular weight polyethylene is melted and crosslinked carbon nanotubes to form a cladding layer with a positive temperature coefficient effect using high temperature dynamic coating technology.

Benefits of technology

When a lithium battery is short-circuited or thermally runaway, the ultra-high molecular weight polyethylene of the cladding melts and causes stress deformation, destroying the conductive network of the carbon nanotubes, causing the material resistance to a sharp increase, blocking the short-circuit current, and improving the safety performance of the lithium battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650647A_ABST
    Figure CN119650647A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a high-safety ternary polymer and a lithium battery, which comprises the following steps of: weighing and mixing a base material, ultrahigh molecular weight polyethylene and a carbon nano tube according to a certain proportion, and uniformly mixing the mixed material by using a high-speed mixer; adding the mixed material into a high-temperature coating machine, setting the heating temperature, the stirring speed and the heat preservation time, dynamically heating the mixed material to melt the ultra-high molecular weight polyethylene, and coating the surface of the base material with the molten ultra-high molecular weight polyethylene crosslinked carbon nanotube material; and after cooling, carrying out roll breaking and sieving on the material to obtain the high-safety ternary polymer. When the lithium battery is short-circuited and releases heat, crystals in the ultra-high molecular weight polyethylene of the coating layer are fused and generate stress deformation, the conductive carbon tube network is disrupted, the PTC effect is formed, the resistance is increased, the short-circuit current of the lithium battery is blocked, and the safety of the lithium battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium batteries, and in particular relates to a method for preparing a high-safety ternary polymer and a lithium battery. Background Art

[0002] Ternary polymer lithium batteries have the characteristics of high energy density and high rate. Therefore, under extreme test conditions such as puncture and overcharging, they may cause dangers such as fire and explosion. In actual applications, lithium batteries may experience short-circuit thermal runaway due to circuit aging and mechanical damage, which may lead to dangers such as fire and explosion.

[0003] In order to improve the safety performance of lithium batteries, there are currently solutions such as high-safety diaphragms, high-safety electrolytes and PTC tabs. However, these solutions all start from the lithium battery system and use auxiliary means to improve the safety performance of lithium batteries under extreme conditions. They do not directly improve the safety performance of ternary polymer positive electrode materials, making the safety risk of ternary polymer lithium batteries still greater than that of lithium iron phosphate battery systems with lower energy density. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the prior art, solve the problems raised in the background technology, and provide a method for preparing a high-safety ternary polymer and a lithium battery.

[0005] The object of the present invention is achieved in this way: a method for preparing a high-safety ternary polymer comprises the following steps:

[0006] Step S1: weigh and mix the base material, ultra-high molecular weight polyethylene and carbon nanotubes according to a certain proportion, and use a high-speed mixer to mix the mixture evenly;

[0007] Step S2: adding the mixed material to a high-temperature coating machine, setting the heating temperature, stirring speed and holding time, dynamically heating the mixed material to melt the ultra-high molecular weight polyethylene, and coating the melted ultra-high molecular weight polyethylene cross-linked carbon nanotube material onto the surface of the base material;

[0008] Step S3: After cooling, the material is rolled and sieved to obtain a high-safety ternary polymer.

[0009] In step S1, the matrix material is Li(Ni x Co y Mn z )O2, where x+y+z=1, 0.5≤x≤0.95, 0≤y≤0.2.

[0010] The ultra-high molecular weight polyethylene has a molecular weight between 1.5 million and 5.5 million, a molecular formula of —(—CH2-CH2—)—n—, a single chain molecule without branches, a particle size of 120±50 μm, and an amount of the ultra-high molecular weight polyethylene that accounts for 3% to 15% of the base material.

[0011] The carbon nanotubes are multi-walled carbon nanotubes, and the amount of the multi-walled carbon nanotubes is 0.5% to 5.0% of the base material.

[0012] The high-speed mixer has a size of 20L, and the mixing speed increases in a step-by-step manner, which are 200 / 500 / 1500rpm respectively. The mixing time of each section is 5 to 15 minutes. The materials are mixed evenly without color difference or white spots.

[0013] In step S2, the high temperature coating machine includes a heating chamber, a stirring blade, a stirring shaft, a sealing upper cover and a motor.

[0014] The high-temperature coating machine has a heating temperature of 150-300° C., a heat preservation time of 10-60 min, a stirring speed of 100-300 rpm, and a blade tip linear speed of 1-10 m / s.

[0015] A lithium battery comprises a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and an aluminum shell. The positive electrode sheet slurry formula is a conductive agent, PVDF (polyvinylidene fluoride), NMP (N-methylpyrrolidone) and the high-safety ternary polymer mentioned above.

[0016] The beneficial effects of the present invention are as follows: a method for preparing a high-safety ternary polymer and a lithium battery is proposed. A layer of ultra-high molecular weight polyethylene and a carbon tube material with enhanced conductivity are compounded on the surface of the positive electrode material by high-temperature dynamic coating. When the lithium battery releases heat due to a short circuit, the crystals in the ultra-high molecular weight polyethylene coating layer melt and produce stress deformation, disrupting the conductive carbon tube network, forming a PTC effect, increasing the resistance, blocking the short-circuit current of the lithium battery, and improving the safety of the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a SEM image of a high-safety ternary polymer and a method for preparing a lithium battery of the present invention.

[0018] Figure 2 This is a structural diagram of a high-temperature coating machine for a method for preparing a high-safety ternary polymer and a lithium battery of the present invention.

[0019] Figure 3 This is a diagram of the power-off test data of Example 1 of a method for preparing a high-safety ternary polymer and lithium battery of the present invention.

[0020] Figure 4This is a diagram of the power-off test data of Example 2 of a method for preparing a high-safety ternary polymer and lithium battery of the present invention.

[0021] In the figure: 1, heating chamber 2, stirring blade 3, stirring shaft 4, sealing cover 5, motor. DETAILED DESCRIPTION

[0022] The present invention will be further described below in conjunction with the accompanying drawings.

[0023] Example 1

[0024] A method for preparing a high-safety ternary polymer comprises the following steps:

[0025] Step S1: weigh and mix the base material, ultra-high molecular weight polyethylene and carbon nanotubes according to a certain proportion, and use a high-speed mixer to mix the mixture evenly;

[0026] Step S2: adding the mixed material to a high-temperature coating machine, setting the heating temperature, stirring speed and holding time, dynamically heating the mixed material to melt the ultra-high molecular weight polyethylene, and coating the melted ultra-high molecular weight polyethylene cross-linked carbon nanotube material onto the surface of the base material;

[0027] Step S3: After cooling, the material is rolled and sieved to obtain a high-safety ternary polymer.

[0028] Furthermore, in step S1, the matrix material is Li(Ni x Co y Mn z )O2, where x+y+z=1, 0.5≤x≤0.95, 0≤y≤0.2.

[0029] Furthermore, the ultra-high molecular weight polyethylene has a molecular weight between 1.5 million and 5.5 million, a molecular formula of —(—CH2-CH2—)—n—, a single chain molecule without branches, a particle size of 120±50μm, and an amount of 3% to 15% of the base material. Ultra-high molecular weight polyethylene is selected with a relative molecular weight of ≥1.5 million, a single chain structure without branches, a large length of a single polymer molecule chain, and a lamellar structure. With carbon nanotubes, it has good conductivity at room temperature, and the lamellar structure dissolves at high temperature, the molecular chain produces stress deformation, destroys the conductive network, and makes the material have a good PTC effect (Positive Temperature Coefficient)

[0030] Furthermore, the carbon nanotubes are multi-walled carbon nanotubes, which have lower cost and their usage accounts for 0.5% to 5.0% of the base material.

[0031] Furthermore, the high-speed mixer has a size of 20L, and the mixing speed is stepped up to 200 / 500 / 1500rpm, respectively, and the mixing time of each section is 5 to 15min. The materials are mixed evenly without color difference or white spots. The high-speed mixer is used for premixing to evenly mix the matrix material, ultra-high molecular weight polyethylene and carbon nanotubes, so as to facilitate the subsequent high-temperature coating.

[0032] Furthermore, in step S2, the high temperature coating machine includes a heating chamber, a stirring blade, a stirring shaft, a sealing upper cover and a motor. This equipment has heating and heat preservation and dynamic stirring functions. The material can be stirred by the shape of the stirring blade. During the stirring process, the material rubs against the inner wall of the chamber, so that the molten polyethylene material is cross-linked with the carbon nanotubes and coated on the surface of the base material to form a coating layer with good conductive properties.

[0033] Furthermore, the heating temperature of the high-temperature coating machine is 150-300° C., the insulation time is 10-60 min, the stirring speed is 100-300 rpm, and the linear speed of the blade tip is 1-10 m / s.

[0034] A lithium battery comprises a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and an aluminum shell. The positive electrode sheet slurry formula is a conductive agent, PVDF (polyvinylidene fluoride), NMP (N-methylpyrrolidone) and the high-safety ternary polymer mentioned above.

[0035] The present invention directly coats the surface of the ternary polymer positive electrode material with an organic ultra-high molecular weight polymer coating layer having a PTC effect, and cross-links the carbon nanotubes to enhance the electrical conductivity of the material at room temperature and reduce the interface resistance of the material.

[0036] The lithium battery made of the high-safety ternary polymer produced by the method, once a short circuit or thermal runaway occurs, the coating layer on the surface of the positive electrode material is heated, the lamellar structure in the ultra-high molecular weight polyethylene is dissolved, and the molecular chain produces stress deformation, destroying the carbon nanotube conductive network therein, so that the surface resistance of the material increases sharply, blocking the conduction of the internal current of the lithium battery, preventing the diffusion and spread of the short circuit and thermal runaway of the lithium battery, and greatly improving the safety performance of the lithium battery.

[0037] Example 2

[0038] A method for preparing a high-safety ternary polymer comprises the following steps:

[0039] Step S1: weigh and mix the base material, ultra-high molecular weight polyethylene and carbon nanotubes according to a certain proportion, and use a high-speed mixer to mix the mixture evenly;

[0040] Step S2: adding the mixed material to a high-temperature coating machine, setting the heating temperature, stirring speed and holding time, dynamically heating the mixed material to melt the ultra-high molecular weight polyethylene, and coating the melted ultra-high molecular weight polyethylene cross-linked carbon nanotube material onto the surface of the base material;

[0041] Step S3: After cooling, the material is rolled and sieved to obtain a high-safety ternary polymer.

[0042] Furthermore, in step S1, the matrix material is Li(Ni x Co y Mn z )O2, where x+y+z=1, 0.5≤x≤0.95, 0≤y≤0.2.

[0043] Furthermore, the ultra-high molecular weight polyethylene has a molecular weight between 1.5 million and 5.5 million, a molecular formula of —(—CH2-CH2—)—n—, a single chain molecule without branches, a particle size of 120±50μm, and an amount of 3% to 15% of the base material. Ultra-high molecular weight polyethylene is selected with a relative molecular weight of ≥1.5 million, a single chain structure without branches, a large length of a single polymer molecule chain, and a lamellar structure. With carbon nanotubes, it has good conductivity at room temperature, and the lamellar structure dissolves at high temperature, the molecular chain produces stress deformation, destroys the conductive network, and makes the material have a good PTC effect (Positive Temperature Coefficient)

[0044] Furthermore, the carbon nanotubes are multi-walled carbon nanotubes, which have lower cost and their usage accounts for 0.5% to 5.0% of the base material.

[0045] Furthermore, the high-speed mixer has a size of 20L, and the mixing speed is stepped up to 200 / 500 / 1500rpm, respectively, and the mixing time of each section is 5 to 15min. The materials are mixed evenly without color difference or white spots. The high-speed mixer is used for premixing to evenly mix the matrix material, ultra-high molecular weight polyethylene and carbon nanotubes, so as to facilitate the subsequent high-temperature coating.

[0046] Furthermore, in step S2, the high temperature coating machine includes a heating chamber, a stirring blade, a stirring shaft, a sealing upper cover and a motor. This equipment has heating and heat preservation and dynamic stirring functions. The material can be stirred by the shape of the stirring blade. During the stirring process, the material rubs against the inner wall of the chamber, so that the molten polyethylene material is cross-linked with the carbon nanotubes and coated on the surface of the base material to form a coating layer with good conductive properties.

[0047] Furthermore, the heating temperature of the high-temperature coating machine is 150-300° C., the insulation time is 10-60 min, the stirring speed is 100-300 rpm, and the linear speed of the blade tip is 1-10 m / s.

[0048] A lithium battery comprises a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and an aluminum shell. The positive electrode sheet slurry formula is a conductive agent, PVDF (polyvinylidene fluoride), NMP (N-methylpyrrolidone) and the high-safety ternary polymer mentioned above.

[0049] The present invention directly coats the surface of the ternary polymer positive electrode material with an organic ultra-high molecular weight polymer coating layer having a PTC effect, and cross-links the carbon nanotubes to enhance the electrical conductivity of the material at room temperature and reduce the interface resistance of the material.

[0050] The lithium battery made of the high-safety ternary polymer produced by the method, once a short circuit or thermal runaway occurs, the coating layer on the surface of the positive electrode material is heated, the lamellar structure in the ultra-high molecular weight polyethylene is dissolved, and the molecular chain produces stress deformation, destroying the carbon nanotube conductive network therein, so that the surface resistance of the material increases sharply, blocking the conduction of the internal current of the lithium battery, preventing the diffusion and spread of the short circuit and thermal runaway of the lithium battery, and greatly improving the safety performance of the lithium battery.

[0051] The following examples further illustrate:

[0052] Example 1:

[0053] Step 1: Prepare the matrix material Li(Ni 0.6 Co 0.1 Mn 0.3 )O2, ultra-high molecular weight polyethylene and carbon nanotubes are weighed and mixed in the ratio of 950g, 40g and 10g, and the mixture is mixed with a high-speed mixer according to the parameters of 200rpm*5min+500rpm*5min+1500rpm*5min; the mixed materials are added into a high-temperature coating machine, and the heating temperature is set to 180°C, the stirring speed is set to 200rpm and the insulation time is set to 30min, the mixture is dynamically heated to melt the ultra-high molecular weight polyethylene, and the molten ultra-high molecular weight polyethylene cross-linked carbon nanotube material is coated on the surface of the base material; after cooling, the material is rolled through a 200-mesh sieve to obtain a high-safety ternary polymer.

[0054] Step 2: The ternary polymer prepared in step 1 is subjected to a charge-off performance test. The charge-off test data is as follows: Figure 3 , 0.2CD discharge capacity reaches 175mAh / g. When the coating is of appropriate amount, the material can exert a higher gram capacity.

[0055] Example 2:

[0056] Step 1: Prepare the matrix material Li(Ni 0.6 Co 0.0 Mn 0.4 )O2, ultra-high molecular weight polyethylene and carbon nanotubes are weighed and mixed in a ratio of 880g, 100g and 20g, and the mixture is mixed by a high-speed mixer according to the parameters of 200rpm*5min+500rpm*5min+1500rpm*5min; the mixed material is added to a high-temperature coating machine, and the heating temperature is set to 220°C, the stirring speed is 200rpm and the insulation time is 60min, and the mixed material is dynamically heated to melt the ultra-high molecular weight polyethylene, and the melted ultra-high molecular weight polyethylene cross-linked carbon nanotube material is coated on the surface of the base material; after cooling, the material is rolled through a 100-mesh sieve to obtain a high-safety ternary polymer. This scheme uses more polyethylene as a coating agent. After the composite material particles present a larger particle size due to the cross-linking effect of polyethylene, so the sieve mesh number is reduced to ensure smooth sieving of the material.

[0057] Step 2: The ternary polymer prepared in step 1 is subjected to a charge-off performance test. The charge-off test data is as follows: Figure 4 , 0.2CD discharge capacity reaches 163mAh / g. Under the premise of adding more coatings, the material still releases a higher gram capacity.

[0058] The ternary polymers prepared in Examples 1 and 2 were directly assembled into button batteries without adding diaphragms, lithium sheets and electrolytes, and heated. The resistance changes were monitored in real time, and it was observed that the resistance of the material increased with the temperature, confirming that the material of the present invention has thermosensitive properties.

[0059] Material Resistance (25℃) Resistance (100℃) Resistance (150℃) Example 1 14.8Ω 9.3Ω 1.2kΩ Example 2 12.0Ω 5.4Ω 1.8kΩ

[0060] Example 3:

[0061] Step 1: Prepare the matrix material Li(Ni 0.6 Co 0.0 Mn 0.4 )O2, ultra-high molecular weight polyethylene and carbon nanotubes are weighed and mixed in a ratio of 3600g, 340g and 60g, and the mixture is evenly mixed using a high-speed mixer according to the parameters of 200rpm*5min+500rpm*5min+1500rpm*15min; the mixed materials are added into a high-temperature coating machine, and the heating temperature is set to 200°C, the stirring speed is set to 250rpm and the insulation time is set to 40min, the mixture is dynamically heated to melt the ultra-high molecular weight polyethylene, and the molten ultra-high molecular weight polyethylene cross-linked carbon nanotube material is coated on the surface of the base material; after cooling, the material is rolled several times and then passed through a 200-mesh sieve to obtain a high-safety ternary polymer.

[0062] Step 2: The ternary polymer prepared in step 1 was mixed with PVDF, SP and NMP in a ratio of 97.5:0.8:0.5:1.2 to prepare a positive electrode slurry and coated to prepare a positive electrode sheet, and then mixed with a negative electrode sheet, a separator, an electrolyte and an aluminum shell to prepare a 40135 cylindrical battery for a needle puncture test. The experimental results showed that after the battery temperature rose to 138°C after the needle puncture, the voltage drop continued to decrease, and the battery did not catch fire or explode. The high-safety ternary polymer material effectively prevented the short-circuit thermal runaway caused by the needle puncture.

Claims

1. A method for preparing a high-safety ternary polymer, characterized in that: The following steps are involved: Step S1: weigh and mix the base material, ultra-high molecular weight polyethylene and carbon nanotubes according to a certain proportion, and use a high-speed mixer to mix the mixture evenly; Step S2: adding the mixed material to a high-temperature coating machine, setting the heating temperature, stirring speed and holding time, dynamically heating the mixed material to melt the ultra-high molecular weight polyethylene, and coating the melted ultra-high molecular weight polyethylene cross-linked carbon nanotube material onto the surface of the base material; Step S3: After cooling, the material is rolled and sieved to obtain a high-safety ternary polymer.

2. The method for preparing a high-safety ternary polymer according to claim 1, characterized in that: In step S1, the matrix material is Li(Ni x Co y Mn z )O2, where x+y+z=1, 0.5≤x≤0.95, 0≤y≤0.

2.

3. The method for preparing a high-safety ternary polymer according to claim 2, characterized in that: The ultra-high molecular weight polyethylene has a molecular weight between 1.5 million and 5.5 million, a molecular formula of —(—CH2-CH2—)—n—, a single chain molecule without branches, a particle size of 120±50 μm, and an amount of the ultra-high molecular weight polyethylene that accounts for 3% to 15% of the base material.

4. The method for preparing a high-safety ternary polymer according to claim 3, characterized in that: The carbon nanotubes are multi-walled carbon nanotubes, and the amount of the multi-walled carbon nanotubes is 0.5% to 5.0% of the base material.

5. The method for preparing a high-safety ternary polymer according to claim 4, characterized in that: The high-speed mixer has a size of 20L, and the mixing speed increases in a step-by-step manner, namely 200 / 500 / 1500 rpm, and the mixing time for each section is 5 to 15 minutes.

6. The method for preparing a high-safety ternary polymer according to claim 1, characterized in that: In step S2, the high temperature coating machine includes a heating chamber, a stirring blade, a stirring shaft, a sealing upper cover and a motor.

7. The method for preparing a high-safety ternary polymer according to claim 6, characterized in that: The high-temperature coating machine has a heating temperature of 150-300° C., a heat preservation time of 10-60 min, a stirring speed of 100-300 rpm, and a blade tip linear speed of 1-10 m / s.

8. A lithium battery comprising a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and an aluminum shell, characterized in that: The positive electrode sheet slurry formula is a conductive agent, PVDF (polyvinylidene fluoride), NMP (N-methylpyrrolidone) and a high-safety ternary polymer as described in any one of claims 1-7.